2021
DOI: 10.1126/sciimmunol.abc6424
|View full text |Cite
|
Sign up to set email alerts
|

Highly immunogenic cancer cells require activation of the WNT pathway for immunological escape

Abstract: Activation of the WNT pathway allows highly immunogenic cancer cells to escape antitumor immunity and induce cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 55 publications
(75 reference statements)
3
48
1
Order By: Relevance
“…SPHK1 induces T cell failure and upregulates the PD-1 ligand, creating an immunosuppressive TME (38,39). Similarly, activation of Wnt/β-catenin, MDM2/ p53, and YAP1 signaling leads to immunosuppression, and blocking such signaling can improve the efficacy of ICIs (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…SPHK1 induces T cell failure and upregulates the PD-1 ligand, creating an immunosuppressive TME (38,39). Similarly, activation of Wnt/β-catenin, MDM2/ p53, and YAP1 signaling leads to immunosuppression, and blocking such signaling can improve the efficacy of ICIs (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report to comprehensively describe the transcriptomic landscape of tumors (specifically related to PD-1 blockade) among patients with MSI-H/dMMR GI tumors. First, our study revealed that non-responders exhibited enrichment of the EMT, angiogenesis, hypoxia, mTORC1, KRAS, Wnt/β-catenin, TGF-β, and various metabolism-related signaling pathways, all of which have been associated with an immunosuppressive TME (11,(18)(19)(20)(21)(22)(23)(24)(25). On the other hand, the IFN-γ pathway was upregulated in responders, which was in line with previous studies showing that an IFN-γ-related mRNA profile correlated with favorable clinical outcomes with ICIs in several malignancies (26).…”
Section: Discussionmentioning
confidence: 89%
“…It is notable that most immuno-suppressive genes were negatively related to m7G scores through 33 cancers, such as famous drug targets PD1 (gene: PDCD1 , ≥30 cancers), CTLA4 (gene: CTLA4 , ≥27 cancers) and the next immune checkpoint receptor LAG3 ( Ruffo et al, 2019 ) (gene: LAG3 , ≥27 cancers). Considering the important role of TGF-β1 and Wnt/β-catenin signaling modulating anticancer immune response ( Yoshimura and Muto, 2011 ; Sheng et al, 2015 ; Pai et al, 2017 ; Takeuchi et al, 2021 ), we investigated the correlations of m7G scores and genes involved in those two signaling pathways ( Figures 6A,B ). UBE2D3, APC, SMAD1, BMPR1A, CTNNB1 , and MAP3K7 in TGF-β1 signaling pathway, showed positive correlation with m7G scores through most cancer types (≥30 cancers), while ADAM17, HDAC2, MAML1, CTNNB1, SKP2, MYC and CUL1 in Wnt/β-catenin signaling positively correlated with m7G scores among most cancer types (≥30 cancers).…”
Section: Resultsmentioning
confidence: 99%